THE IMPACTS OF CHARACTERISTICS OF HOMETOWN CONNECTEDNESS BETWEEN AUDITORS AND EXECUTIVES ON AUDIT QUALITY: EVIDENCE FROM CHINA - Yuan, Deli; Gazi, Md. Abu Issa; Liu, Guangrui; Chen, Xiaolin; Alam, Mohammad Nurul (International Journal of Accounting & Finance Review, 2023)
Quality audit depends on the qualified audit team. Hometown connectedness affects audit quality among executives and auditors. Higher auditor-executive hometown connectivity degrades audit quality more. The present study aimed to analyse and test the influence of the strength and density of auditors-managers hometown connectedness on audit quality. Panel data research methods were employed here. The data is analyzed using the Regression model, including the Logit regression model and OLS regression model, Pearson correlation coefficients, χ2 grouping test and Heckman two-step regression, by using 3674 observations of the Chinese Stock markets from 2008 to 2020 and from the perspective of sociology and economics that were reserved over 15 different industries and the auditor-manager hometown connectivity involved 25 different provinces. The present study reveals that the auditors-manager’s hometown connectedness has a negative effect on audit quality. The influence degree increases along with the strength of the auditors-manager’s hometown connectedness. Secondly, the influence degree increases along with the density of auditors-managers hometown connectedness. Finally, some suggestions related to audit quality supervision are put forward. The above findings are still valid after controlling for potential endogenous problems. The research on the relationship between auditors-managers’ hometown connectedness and audit quality is extended and deepened. The present study’s findings apply to auditors and executives in that a bias-free relationship is essential to carry out an influence-free audit process. Audit organizations and business organizations can benefit from this research. JEL Classification Codes: D73, F65, G32, H54, L32, M41.